Prison Reform USA - Prison Reform USA (2014)
"Prison Reform USA is an organization based out of Atlanta, Georgia. It was created by Amy Valeed in 2014. After her cousin was unfairly imprisoned for distribution of cocaine, she got to know the American prison system very well. She started to see all of the injustices involved with the prison system in the USA, and she formed this organization"